Agenda Lecture Content Recurrence Relations Solving Recurrence Relations

  • Slides: 39
Download presentation
Agenda • Lecture Content: § Recurrence Relations § Solving Recurrence Relations § Iteration §

Agenda • Lecture Content: § Recurrence Relations § Solving Recurrence Relations § Iteration § Linear homogenous recurrence relation of order k with constant coefficients • Exercise

Recurrence Relations

Recurrence Relations

Recurrence Relations § Relates the n-th element of a sequence to its predecessors. Example:

Recurrence Relations § Relates the n-th element of a sequence to its predecessors. Example: an = 9 * an-1 § Closely related to recursive algorithms. § Suited for analysis of algorithm

Recurrence Relations § Generate a sequence : 1. Start with 5 2. Given any

Recurrence Relations § Generate a sequence : 1. Start with 5 2. Given any term, add 3 to get the next term 5, 8, 11, 14, … § Sequence {an} = a 0, a 1, …, an-1, an 1. a 0= 5 initial condition 2. an = an-1 + 3 , n ≥ 1 recurrence relation

Recurrence Relations for the sequence {an} § is an equation that expresses an in

Recurrence Relations for the sequence {an} § is an equation that expresses an in terms of one or more of the previous terms of the sequence, namely, a 0, a 1, …, an-1 for all integers n with n ≥ n 0, where n 0 is a nonnegative integer. § A sequence {an} is called a solution of a recurrence relation if its terms an satisfy the recurrence relation.

Motivation One of the main reason for using recurrence relation is that sometimes it

Motivation One of the main reason for using recurrence relation is that sometimes it is easier to determine the n-th term of a sequence in terms of its predecessors than it is to find an explicit formula for the n-th term in terms of n.

Example § Let {an} be a sequence that satisfies the recurrence relation an =

Example § Let {an} be a sequence that satisfies the recurrence relation an = an-1 – an-2 for n = 2, 3, 4, … and suppose that a 0 = 3 and a 1 = 5. What are a 2 and a 3? § a 2 = a 1 – a 0 = 5 – 3 = 2 § a 3 = a 2 – a 1 = 2 – 5 = -3 § Also a 4, a 5, …

Exercises § Find the first six terms of the sequence defined by the following

Exercises § Find the first six terms of the sequence defined by the following recurrence relations: an = an-1 + an-3 a 0 = 1, a 1 = 2, a 2 = 0 an = n. an-1 + (an-2)2 a 0 = -1, a 1 = 0

Example § Find the recurrence relation of: - {an} = (0, 1, 2, 3,

Example § Find the recurrence relation of: - {an} = (0, 1, 2, 3, …) - {an} = (5, 10, 15, 20, …) § Find the first three terms of the sequence defined by the following recurrence relations: - an = 3 * an-1 – an-2 a 0 = 3 and a 1 = 5 - an = an-1 – an-2 + an-3 a 0 = 3, a 1 = 5 and a 2 = 5

Modelling with Recurrence Relations (1) § The number of bacteria in a colony doubles

Modelling with Recurrence Relations (1) § The number of bacteria in a colony doubles every hour. If a colony begins with five bacteria, how many will be present in n hours? - a 0 = 5 - a 1 = 10 - a 2 = 20 - … § The number of bacteria at the end of n hours: an = 2 * an-1

Modelling with Recurrence Relations (2) § Suppose that a person deposits $ 10, 000

Modelling with Recurrence Relations (2) § Suppose that a person deposits $ 10, 000 in a saving account at a bank yielding 11% per year with interest compounded annually. How much will be in the account after 30 years? • • • Pn : the amount in the account after n years Pn = Pn-1 + 0. 11 Pn-1 = 1. 11 Pn-1 P 0 = 10, 000 P 1 = 1. 11 P 0 P 2 = 1. 11 P 1 = 1. 11 * 1. 11 P 0 = (1. 11)2 P 0 Pn = (1. 11)n P 0 Deriving explicit formula from the recurrence relation and its initial condition (Section 7. 2)

Converting to a Recursive Algorithm § § A recursive function is a function that

Converting to a Recursive Algorithm § § A recursive function is a function that invokes itself. A recursive algorithm is an algorithm that contains a recursive function Input: n, the number of years Output: the amount of money at the end of n years 1. 2. 3. 4. 5. compound_interest (n){ if (n == 0) return 10, 000 return 1. 11 * compound_interest (n-1) }

Modeling with Recurrence Relation (3) § A young pair of rabbits is placed on

Modeling with Recurrence Relation (3) § A young pair of rabbits is placed on an island. A pair of rabbit does not breed until they are 2 months old. After they are 2 months old, each pair of rabbits produces another pair each month. Find a recurrence relation for the number of pairs of rabbit on the island after n months, assuming that no rabbits ever die. § fn : the number of pairs of rabbits after n months

Modeling with Recurrence Relation (3) Month reproducing pairs young pairs total pairs 1 0

Modeling with Recurrence Relation (3) Month reproducing pairs young pairs total pairs 1 0 1 1 2 0 1 1 3 1 1 2 4 1 2 3 5 6 3 5 8

Modeling with Recurrence Relation (3) § fn : the number of pairs of rabbits

Modeling with Recurrence Relation (3) § fn : the number of pairs of rabbits after n months § f 1 = 1 § f 2 = 1 § f 3 = 2 § fn = the number on the island for the previous month + the number of newborn pairs § fn = fn-1 + fn-2 Fibonacci Numbers

Modelling with Recurrence Relation (4) § Find a recurrence relation and give initial conditions

Modelling with Recurrence Relation (4) § Find a recurrence relation and give initial conditions for the number of bit strings of length n that do not have two consecutives 0 s. § an : the number of bit strings of length n that do not have two consecutive 0 s.

The Tree Diagrams How many bit strings of length four do not have two

The Tree Diagrams How many bit strings of length four do not have two consecutive 0 s? bit ke-1 bit ke-2 bit ke-3 1 1 0 0 1 1 1 0 There are eight bit strings bit ke-4 0 1 1 0 1

Modelling with Recurrence Relation (4) an = an-1 + an-2 for n ≥ 3

Modelling with Recurrence Relation (4) an = an-1 + an-2 for n ≥ 3 § § a 1 = 2 0, 1 a 2 = 3 (01, 10, 11) a 3 = 5 (011, 010, 101, 110, 111) a 4 = 8

Solving Recurrence Relations

Solving Recurrence Relations

Solving Recurrence Relations - Given recurrence relations with sequence: a 0 , a 1

Solving Recurrence Relations - Given recurrence relations with sequence: a 0 , a 1 , … - Find an explicit formula for the general term: an - Two methods: - Iteration - Recurrence relations with constant coefficients

Iteration Steps: - Use the recurrence relation to write the n-th term an in

Iteration Steps: - Use the recurrence relation to write the n-th term an in terms of certain of its predecessors an-1 , …, a 0 - Use the recurrence relation to replace each of an-1 , … by certain of their predecessors. - Continue until an explicit formula is obtained.

Iteration: Example 1 an = an-1 + 3 a 0= 5 n≥ 1 Solution:

Iteration: Example 1 an = an-1 + 3 a 0= 5 n≥ 1 Solution: - an-1 = an-2 + 3 - an = an-1 + 3 = (an-2 + 3) + 3 = an-2 + 2. 3 = (an-3 + 3) +2. 3 = an-3 + 3. 3 = an-k + k. 3 …k=n = a 0 + n. 3 =5+n. 3

Iteration: Example 2(1) § The number of bacteria in a colony doubles every hour.

Iteration: Example 2(1) § The number of bacteria in a colony doubles every hour. If a colony begins with five bacteria, how many will be present in n hours? § a 0 = 5 § a 1 = 10 § a 2 = 20 § … § The number of bacteria at the end of n hours: an = 2 * an-1

Iteration: Example 2(2) an = 2 * an-1 = 2 * (2 * an-2

Iteration: Example 2(2) an = 2 * an-1 = 2 * (2 * an-2 ) = 2 * 2 ( an-2 ) = 2 * (2 * an-3 ) = 23 ( an-3 ) … = 2 n * a 0 = 2 n * 5

Iteration: Example 3 § The deer population is 1000 at time n = 0

Iteration: Example 3 § The deer population is 1000 at time n = 0 § The increase from time n-1 to time n is 10 percent. § Find the recurrence relation, initial condition and solve the recurrence relation at time n § § § a 0 = 1000 an = 1. 1 * an-1 an = 1. 1 * (1. 1 * an-2) = 1. 12 * an-2 an = 1. 1 n * a 0 an = 1. 1 n * 1000

Recurrence Relations with Constant Coefficients

Recurrence Relations with Constant Coefficients

Definition § A linear homogeneous recurrence relation of order k with constant coefficients is

Definition § A linear homogeneous recurrence relation of order k with constant coefficients is a recurrence relation of the form: an = c 1 an– 1+ c 2 an– 2+ … + ckan–k , ck ≠ 0 § Example: • Sn = 2 Sn– 1 • fn = fn– 1 + fn– 2

Not linear homogenous recurrence relations § Example: • an = 3 an– 1 an–

Not linear homogenous recurrence relations § Example: • an = 3 an– 1 an– 2 • an – an– 1 = 2 n • an = 3 nan– 1 Why?

Solving Recurrence Relations § Example: • Solve the linear homogeneous recurrence relations with constant

Solving Recurrence Relations § Example: • Solve the linear homogeneous recurrence relations with constant coefficients an = 5 an– 1 – 6 an– 2 a 0 = 7, a 1= 16 § Solution: • Often in mathematics, when trying to solve a more difficult instance of some problem, we begin with an expression that solved a simpler version.

Solving Recurrence Relations § For the first-order recurrence relation, the solution was of the

Solving Recurrence Relations § For the first-order recurrence relation, the solution was of the form Vn= tn ; thus for our first attempt at finding a solution of the secondorder recurrence relation, we will search for a solution of the form Vn= tn. § If Vn = tn is to solve the recurrence relation, we must have Vn= 5 Vn– 1– 6 Vn– 2 or tn = 5 tn– 1 – 6 tn– 2 or tn – 5 tn– 1+ 6 tn– 2 = 0. Dividing by tn– 2, we obtain the equivalent equation t 2 – 5 t 1 + 6 = 0. Solving this, we find the solutions t= 2, t= 3. Characteristic roots polynomial

Solving Recurrence Relations § We thus have two solutions, Sn = 2 n and

Solving Recurrence Relations § We thus have two solutions, Sn = 2 n and Tn = 3 n. • We can verify that if S and T are solutions of the preceding recurrence relation, then b. S + d. T, where b and d are any numbers, is also a solution of that relation. In our case, if we define the sequence U by the equation Un = b. Sn+ d. Tn = b 2 n + d 3 n, § U is a solution of the given relation.

Solving Recurrence Relations § To satisfy the initial conditions, we must have: 7 =

Solving Recurrence Relations § To satisfy the initial conditions, we must have: 7 = U 0 = b 20 + d 30= b + d, 16 = U 1= b 21+ d 31= 2 b + 3 d. Solving these equations for b and d, we obtain b = 5, d = 2. § Therefore, the sequence U defined by Un= 5∙ 2 n + 2∙ 3 n satisfies the recurrence relation and the initial conditions. § We conclude that an= Un= 5∙ 2 n+ 2∙ 3 n, for n = 0, 1, ….

Theorem § Let an = c 1 an– 1+ c 2 an– 2 be

Theorem § Let an = c 1 an– 1+ c 2 an– 2 be a second-order, linear homogeneous recurrence relation with constant coefficients. • If S and T are solutions of the recurrence relation, then U = b. S+ d. T is also a solution of the relation. • If r is a root of t 2–c 1 t–c 2= 0, then the sequence rn, n = 0, 1, …, is a solution of the recurrence relation. • If a is the sequence defined by the recurrence relation, a 0 = C 0, a 1= C 1, and r 1 and r 2 are roots of the preceding equation with r 1 ≠ r 2, then there exist constants b and d such that an= br 1 n + dr 2 n, n = 0, 1, ….

Example (1) § More Population Growth • Assume that the deer population of Rustic

Example (1) § More Population Growth • Assume that the deer population of Rustic County is 200 at time n = 0 and 220 at time n = 1 and that the increase from time n– 1 to time n is twice the increase from time n– 2 to time n– 1. • Write a recurrence relation and an initial condition that define the deer population at time n and then solve the recurrence relation.

Example (1) § Solution: • Let dn denote the deer population at time n.

Example (1) § Solution: • Let dn denote the deer population at time n. d 0 = 200, d 1 = 220 dn – dn-1 = 2(dn-1 – dn-2) dn = 3 dn-1 – 2 dn-2 • Solving t 2 – 3 t + 2 = 0, we have roots 1 and 2. Then the sequence d is of the form dn = b∙ 1 n + c∙ 2 n = b + c 2 n. • To meet the initial conditions, we must have 200 = d 0= b + c, 220 = d 1= b + 2 c. Solving for b and c, we find b= 180, and c= 20. • Thus, dn is given by dn = 180 + 20∙ 2 n.

Example (2) § Find an explicit formula for the Fibonacci sequence: fn – fn–

Example (2) § Find an explicit formula for the Fibonacci sequence: fn – fn– 1 – fn– 2= 0, n≥ 3 f 1 = 1, f 2 = 1 § Solution: • We begin by using the quadratic formula to solve t 2 –t – 1 = 0. The solutions are t = (1 ±√ 5)/2. Thus the solution is of the form fn= b((1+√ 5)/2)n + c((1–√ 5)/2)n. – To satisfy the initial conditions, we must have b((1+√ 5)/2) + c((1–√ 5)/2)= 1, b((1+√ 5)/2)2+ c((1–√ 5)/2)2= 1. Solving these equations for b and d, we obtain b = 1/√ 5, d = -1/√ 5. • • Therefore, fn= 1/√ 5∙((1+√ 5)/2)n – 1/√ 5((1–√ 5)/2)n.

Theorem § Let an = c 1 an– 1 + c 2 an– 2

Theorem § Let an = c 1 an– 1 + c 2 an– 2 be a second-order, linear homogeneous recurrence relation with constant coefficients. • Let a be the sequence satisfying the relation and a 0 = C 0, a 1= C 1. • If both roots of t 2 – c 1 t – c 2 = 0 are equal to r, then there exist constants b and d such that an = brn + dnrn, n = 0, 1, ….

Example § Solve the recurrence relation dn= 4(dn-1 – dn-2) subject to the initial

Example § Solve the recurrence relation dn= 4(dn-1 – dn-2) subject to the initial conditions d 0= 1 = d 1. – According to theorem, Sn= rn is a solution, where r is a solution of t 2 – 4 t + 4 = 0. Thus we obtain the solution Sn = 2 n. – Since 2 is the only solution of the equation, Tn= n 2 n is also a solution of the recurrence relation. – Thus the general solution is of the form U = a. S+ b. T. – We must have U 0 = 1 = U 1. The last equations become a. S 0 + b. T 0= a+ 0 b= 1, a. S 1+ b. T 1= 2 a+ 2 b = 1. – Solving for a and b, we obtain a = 1, b = -1/2. – Therefore, the solution is dn= 2 n – 1/2 n 2 n = 2 n – n 2 n-1.

Note § For the general linear homogeneous recurrence relation of order k with constant

Note § For the general linear homogeneous recurrence relation of order k with constant coefficients c 1, c 2, …, ck, • if r is a root of tk – c 1 tk-1 – c 2 tk-2 – … – ck = 0 of multiplicity m, it can be shown that rn, nrn, … , nm-1 rn are solutions of the equation.